Cathepsin S levels and survival among patients with non-ST-segment elevation acute coronary syndromes - Stamatelopoulos, Kimon; Müller-Hennessen, Matthias; Georgiopoulos, Georgios; Lopez-Ayala, Pedro; Sachse, Marco; Vlachogiannis, Nikolaos I.; Sopova, Kateryna; Delialis, Dimitrios; Bonini, Francesca; Patras, Raphael; Ciliberti, Giorgia; Vafaie, Mehrshad; et al. (Journal of the American College of Cardiology, 2022)
Patients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS) are at high residual risk for long-term cardiovascular (CV) mortality. Cathepsin S (CTSS) is a lysosomal cysteine protease with elastolytic and collagenolytic activity that has been involved in atherosclerotic plaque rupture. The purpose of this study was to determine the following: 1) the prognostic value of circulating CTSS measured at patient admission for long-term mortality in NSTE-ACS; and 2) its additive value over the GRACE (Global Registry of Acute Coronary Events) risk score.